Paternal adverse childhood experiences and offspring’s attentional disengagement from faces at 8 months—Results from the FinnBrain Birth Cohort Study - Magdalena Klimek; Hasse Karlsson; Linnea Karlsson; Riikka Korja; Saara Nolvi; Tuomo Häikiö; Jetro J. Tuulari; Eeva-Leena Kataja (PLoS ONE, 2025)
Paternal adverse childhood experiences (ACEs) have been recently linked to offspring’s brain development. Yet, none of the previous studies in humans have explored the association between paternal ACEs and a child’s attentional bias for facial expressions of emotion. Our study fills this gap. Data were collected from 239 fathers (mean age 32.15; SD 5.04) and their children at 8 months of age who were part of the FinnBrain Birth Cohort Study. Paternal ACEs were evaluated using the Trauma and Distress Scale (TADS) in five domains: emotional and physical neglect, emotional and physical abuse, and sexual abuse. In children, eye-tracking was used to study attentional engagement to emotional faces vs. non-faces and distractors, and to calculate face and fear bias indices. Hierarchical linear regression and the Mann-Whitney U test were used for analyses. A negative association between paternal sexual abuse and face bias was found in children (p = 0.043), when paternal postpartum anxiety and sex of the child were controlled, however the effect size was rather low. Additionally, daughters (n = 6) of sexually abused fathers expressed lower face bias (p = 0.02) and higher fear bias (p = 0.04) than daughters of sexually non-abused fathers. Our preliminary exploration suggests a potential intergenerational effect of paternal exposure to sexual abuse on the processing of facial expression among daughters at the age of 8 months, yet the results require further confirmatory analyses, especially in a larger study group of ACEs-exposed individuals.